Improvement in Gender and Transgender Knowledge in University Students Through the Creative Factory Methodology - Gorrotxategi, Maitane Picaza; Ozamiz-Etxebarria, Naiara; Jiménez-Etxebarria, Eneritz; Cornelius-White, Jeffrey H. D. (Frontiers in Psychology, 2020)
In Spain, Social Educators, similar to both social workers and educators in the USA, help coordinate social change through educational interventions and mobilization of social groups to benefit marginalized people and overall societal welfare. They are trained to work with diverse populations, and it is important that they have awareness and training on gender and transgender issues given the extensive discrimination that transgender people endue. Research has begun to identify the important role that knowledge and attitudes of health and educational professionals may play in providing a supportive, healing context to combat the harmful effects of this discrimination and how educational trainings may foster improved knowledge and attitudes in helping professions. This study describes a program to improve knowledge and positive attitudes towards gender and especially transgender people in university students who study Social Education. The researchers measured knowledge and attitudes towards gender and transgender people issues of 64 students before and after receiving a four-month interactive training. They used the Short Form of the Genderism and Transphobia Scale, a 12-item scale of transphobia and gender ideology variables. The researchers also asked participants about their knowledge of gender and transgender issues before and after training. The methodological experience “Creative Factory” was employed as an interactive training program. The main goal of this methodology is to enable students in a formative context to analyze social realities to generate discussion and innovate ideas to design successful practices. After four months of training with a weekly session on gender and transgender learning, students showed improvements in knowledge and attitudes towards both gender and transgender people. Specifically, students demonstrated more knowledge about gender and transgender issues and more positive attitudes towards transgender people. The study demonstrates that training in gender education using the Creative Factory methodology improved knowledge and attitudes in students.